Conversion of MeOH and Toluene into Styrene and Ethylbenzene Using Composite Catalysts Containing MeOH Dehydrogenation Components. Issue 6 (20th February 2019) - Han, Qiao; Li, Peidong; Zhang, Yanfei; Lu, Peng; Xu, Li; Guo, Hongchen; Xu, Lei
Abstract: A new strategy, the coupling of methanol dehydrogenation and side‐chain alkylation of toluene, to realize highly effective conversion of methanol and toluene into styrene and ethylbenzene was proposed. A series of composite catalysts were designed by combining CsX with numerous catalysts reported to be effective for methanol dehydrogenation to formaldehyde. The studies of side‐chain alkylation of toluene with methanol over these composite catalysts indicated that the introduction of methanol dehydrogenation components could universally improve the yield of styrene and ethylbenzene in side‐chain alkylation of toluene with methanol. And the introduction of some methanol dehydrogenation components, i. e. sodium borate (Na2 B4 O7 ) and CuO/SiO2, could even double the yield of styrene and ethylbenzene. Furthermore, the influence of the mass ratio of different components and the spatial arrangement of different active sites on composite catalysts was investigated in detail. Abstract : Happy couple ! The coupling of methanol dehydrogenation and side‐chain alkylation of toluene realizes high selective conversion of toluene with methanol into styrene (ST) and ethylbenzene (EB) by composite catalysts combining CsX with methanol dehydrogenation components, wherein the thermodynamic driving force for dehydrogenation of methanol was a key point for the coupling reaction.